2013
DOI: 10.1089/met.2012.0149
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Fetuin-A Levels with Coronary Atherosclerotic Burden and NAFLD in Patients Undergoing Elective Coronary Angiography

Abstract: This prospective cross-sectional study demonstrates high fetuin-A levels to be independently associated with NAFLD and a lower risk of coronarographically diagnosed CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…However, it should be noted that with respect to the role of preventing insulin resistance, it cannot be regarded as the direct factor related to the development of CVDs, since insulin resistance is significantly correlated with the production of insulin and then the abnormality of lipid, whereas the predominant reason for CVDs is atherosclerosis [32]. Aside from its role in preventing insulin resistance, FA also has a relationship with metabolic syndrome, atherogenic dyslipidemia and reduced adiponectin levels, and risk factors for nonalcoholic fatty liver disease and might also be involved in fibrosis of liver [21]. Based on this information, there is an apparent contradiction in the fact that low levels of fetuin-A are associated with CVD while high levels are associated with NAFLD and diabetes [29, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that with respect to the role of preventing insulin resistance, it cannot be regarded as the direct factor related to the development of CVDs, since insulin resistance is significantly correlated with the production of insulin and then the abnormality of lipid, whereas the predominant reason for CVDs is atherosclerosis [32]. Aside from its role in preventing insulin resistance, FA also has a relationship with metabolic syndrome, atherogenic dyslipidemia and reduced adiponectin levels, and risk factors for nonalcoholic fatty liver disease and might also be involved in fibrosis of liver [21]. Based on this information, there is an apparent contradiction in the fact that low levels of fetuin-A are associated with CVD while high levels are associated with NAFLD and diabetes [29, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective research has recognized that low serum FA levels are a valid predictor of CVD [19, 20]. In contrast, controversial opinions have supported the idea that reduced plasma concentrations of FA may increase CVD risk by inducing adipocyte-linked inflammatory cytokines [21, 22]. Because of the existence of contradictory theories on this subject, we conducted the following meta-analysis on downregulated serum FA levels and its contributory effects on CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Ballestri et al . reported that the serum fetuin‐A level is significantly lower in NAFLD patients with CVD than in NAFLD patients without CVD . In addition, they found that elevated serum fetuin‐A levels are an independent negative predictor of CVD.…”
Section: Discussionmentioning
confidence: 98%
“…This inverse relation with fibrosis wasn't reconfirmed in a biopsyproven series, a discrepancy attributed to the outweighing of inflammation in NASH in case of lower degrees of fibrosis [120]. Finally, and in line with a dual role of FetA, NAFLD could be independently associated with FetA, whilst the risk of coronarographically diagnosed CAD decreased [121]. More recent analyses confirm the conflicting CV protective and harmful role of FetA, potentially explained by the balance between promoting a CVD risk profile and the capability to decrease vascular calcifications [122].…”
Section: Hepatokinesmentioning
confidence: 95%